A replacement name for Wilsoniella Pettibone, 1993 (Annelida: Polynoidae), junior homonym of Wilsoniella Khalfin, 1939 (Brachiopoda: Rhynchonellida), and revalidation of Pessoaiella Guimarães, 1940 over Wilsoniella Eichler, 1940 (Phthiraptera: Ischnocera: Philopteridae) also a junior homonym of Wilsoniella Khalfin, 1939 - Nemésio, André (Zootaxa, 2006)
Kellogg (1910) described Lipeurus absitus (Phthiraptera: Philopteridae), a species of chewing louse found on the Hoazin Opisthocomus hoazin (Statius Muller) (Aves: Opisthocomidae), a bird found in the northern South America. Harrison (1916) erected the genus Esthiopterum for several species of Lipeurus, including L. absitus. In 1940, two authors independently recognized that Esthiopterum absitum (Kellogg) should be placed in a genus of its own. Eichler (1940) erected the genus Wilsoniella in 15 May 1940, and Guimarães erected the genus Pessoaiella in a paper published 36 days later, on 20 June 1940. Thus, Wilsoniella Eichler had precedence over Pessoaiella Guimarães. This latter name, as a consequence, has been treat